2009
DOI: 10.1111/j.1468-2389.2009.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Construct and Criterion‐Related Validation of a Measure of Emotional Reasoning Skills: A two‐study investigation

Abstract: In a two-study investigation, the construct and criterion-related validities of the Test of Emotional Intelligence, an ability-based measure of emotional reasoning skills, were examined. In Study 1, as hypothesized, emotional reasoning skills were related to emotion recognition ability (i.e., as measured by Diagnostic Analysis of Nonverbal Accuracy), emotional empathy, and three measures of successful social functioning (i.e., social astuteness, interpersonal influence, and apparent sincerity) assessed by peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 87 publications
1
16
0
3
Order By: Relevance
“…To additionally ensure that we sampled employees working in jobs with complex task demands, we administered a short version of the Environment‐Structure Test (Umwelt‐Struktur‐test; Bergmann & Eder, ; Blickle, Momm, et al, 2009). The test measures Holland's () six general occupational job demands (i.e., realistic, investigative, artistic, social, enterprising, and conventional).…”
Section: Methodsmentioning
confidence: 99%
“…To additionally ensure that we sampled employees working in jobs with complex task demands, we administered a short version of the Environment‐Structure Test (Umwelt‐Struktur‐test; Bergmann & Eder, ; Blickle, Momm, et al, 2009). The test measures Holland's () six general occupational job demands (i.e., realistic, investigative, artistic, social, enterprising, and conventional).…”
Section: Methodsmentioning
confidence: 99%
“…So far, initial steps have been taken to use the SJT format for measuring EI. For instance, some subtests of the MSCEIT (e.g., Emotion Management), the Levels of Emotional Awareness Scale (Lane, Quinlan, Schwartz, Walker, & Zeitlin, 1990), and the Test of Emotional Intelligence (Blickle et al., 2009) consist of SJT‐like items. MacCann and Roberts (2008) have created two full‐blown paper‐and pencil EI SJTs.…”
Section: Assessing Emotional Intelligence With Situational Judgment Tmentioning
confidence: 99%
“…Previous research has demonstrated discriminant validity of TEMINT with General Mental Ability (Amelang & Steinmayr, 2006) and Verbal Intelligence (Blickle, Kramer, & Mierke, 2010). Recently, Blickle, Momm, Kramer, Mierke, Liu, and Ferris (2009) found that TEMINT scores were related to emotion recognition ability, emotional empathy, and effective social functioning. In addition, they reported that the TEMINT scores explained additional variance in overall job performance ratings beyond general mental ability and personality traits.…”
Section: Introductionmentioning
confidence: 99%